Microwave Assisted De-husking of Foxtail Millet - K., Sunil C.; Chacko, Neeraja (Journal of Agricultural Engineering, 2019)
A study was conducted to determine the effect of microwave pre-treatment on de-husking characteristics and quality parameters of foxtail millet. Foxtail millet was treated at three microwave power levels (900 W, 720 W and 540 W) for three different exposure time (120 s, 100 s and 80 s). Increase in grain surface temperature from 64.68ËšC to 81.66ËšC and decrease in de-husking time from 191 s to 88 s were observed with increase in microwave power level and exposure time. De-husking yield increased initially with increase in microwave power and exposure time, reaching a maximum of 85.64 % (720 W, 120 s), and thereafter decreased. The lowest de-husking yield of 72.12 % was observed at 900 W and 100 s exposure time. The increase in broken content from 0.20 % to 19.61 %, and reduction in head yield from 99.80 % to 85.40 % was observed with increase in microwave power and exposure time. The colour change was not significant (@ pâ‰¤0.05) in all the treatments. Cooking time of the de-husked grain decreased with increase in microwave power level and exposure time from 544 s to 442 s. De-husking yield of 91.97 % was predicted at optimal conditions of 732 W microwave power and 80 s exposure time.